Studies on the preparation of stem amaranth pickle (Journal of the Bangladesh Agricultural University, 2014)
Fresh stem amaranth was analyzed for proximate composition and the developed pickles were analyzed for proximate composition, microbiological status, sensory attributes and overall storage stability of the pickles. Pickle was prepareded with sugar, salt, oil and vinegar. Five formulations of stem amaranth were prepared. Fresh stem amaranth contains 96.0% moisture, 1.0% ash, 0.01% fat, 2.0% protein and 30 mg/100g vitamin-C. The chemical analysis of pickles showed that moisture content was highly reduced in all processed samples. The microbiological studies revealed that total viable counts of bacteria and fungal growth were high in the pickles prepared without vinegar and sugar but it was low with vinegar-sugar-oil mix. The panelists marked for colour, flavor, texture and overall acceptability and analyzed statistically. Among five samples, the pickles prepared with vinegar-sugar-oil mix were the best. Storage studies were carried out up to six months at room temperature. Minor change was observed for color and flavor. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21409 J. Bangladesh Agril. Univ. 12(1): 177-182, June 2014